Degradation of 2-chlorobenzoic and 2,5-dichlorobenzoic acids in pure culture by Pseudomonas stutzeri - Kozlovsky, S A; Zaitsev, G M; Kunc, F; Gabriel, J; Boronin, A M (Folia microbiologica, 1993)
A strain of Pseudomonas stutzeri KS25 utilizing 2-chlorobenzoic and 2,5-dichlorobenzoic acids as the sole carbon and energy source was isolated from polychlorophenol-contaminated soil and sewage, using the method of enrichment cultures. This strain was also able to grow on 2-fluoro-, 2-iodo-, 2-bromo- and 2,5-dihydroxybenzoate, but did not utilize 3-, 4-chloro-, 2,4- and 2,6-dichlorobenzoates as the sole carbon and energy source, however, it cometabolized 3-chloro-, 2,4- and 2,6-dichlorobenzoates, but not 4-chlorobenzoate. The yield of released chlorine during utilization of 2-chloro- and 2,5-dichlorobenzoates amounted to 100% of the theoretical. The concentration of 2-chloro- and 2,5-dichlorobenzoates, not substantially inhibiting the isolated microorganism, was within the range 0.25-0.5 and 2.5-3.0 g/L, respectively.
Keywords: Biodegradation, Environmental; chlorbenzoáty; Chlorobenzoates; biodegradace; Pseudomonas